فِقْھُ التَعَامُلِ مَعَ السُّنَّةِ النَّبَوِیَّةِ عِنْدَ الدُّكْتُور یُوسُف القَرَضَاوِي - ساسي, عنتر (University of Eloued-جامعة الوادي, 2015)
In the name of Allah the most compassionate, the most merciful. Thank Allah Almighty and peace and prayer upon the prophet Muhammad. Our prophet Sunnah plays an Important role in our life as Muslims because it is the scientific path and practical part of Shariia interpretations, besides; it includes some characteristics and features which make it up to date everywhere and and every time. Despite it faces difficulties and challenges which in turn lead to its decline, but with Allah help and support, some people like preachers and scholars bear the responsibility to defend this religion, those armed with patience, science, Fireh and take their role to demarcate laws and grounding rules in order to protect the purified Sunnah from any inconveniences people have caused. One from the pioneers who courageously defend it from its enemies is Doctor Youcef Elgaradaoui who most importantly contributed to define some landmarks and limits that orients and guides the best understanding of Islam and how to politely deal with our prophet Sunnah and to successfully fulfill its duty in life as it did in the past.
مذكرة ماستر
Keywords: السُّنَّةِ النَّبَوِیَّةِ / فِقْھُ التَعَامُلِ / یُوسُف القَرَضَاوِي; The Sunnah / Jurisprudence / Yusuf Al-Qaradawi